Comparative effect of different types of artificial teeth and the effect of different surface treatments on the shear bond strength to CAD/CAM denture base - Saleh, Hajar M.; Al-Noori, Ammar Kh. (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: Complete tooth loss reduces a patient’s quality of life. The most suitable treatment option is complete denture fabrication, which provides an acrylic-based removable prosthesis as a substitute for all dentition and related structures. Purpose: This study aims to evaluate the shear bond strength (SBS) of three types of artificial teeth—acrylic, composite, and computer-aided design and computer-aided manufacturing (CAD/CAM) milled denture teeth—and the effects of three surface treatments: bur roughening, air abrasion (AB), and dichloromethane (DCM). Methods: Milled CAD/CAM denture base resin was used to test three types of denture teeth: acrylic, composite, and milled CAD/CAM. A total of 120 maxillary right central incisors were used, with 40 of each tooth type. Each type was divided into four groups based on the treatment surface: control (no treatment), AB, bur roughening, and DCM. Universal testing equipment was used to measure SBS. Data were statistically analyzed using ANOVA, and Duncan’s multiple range test was applied to compare mean values among groups. Results: Acrylic and CAD/CAM milled teeth demonstrated higher SBS compared with composite teeth. Teeth treated with AB and DCM surface treatments exhibited increased SBS across all tooth types compared with the control groups. Conclusion: Acrylic and CAD/CAM milled teeth show superior SBS compared with composite teeth. AB and DCM treatments effectively enhance SBS in all types of teeth.